Skin Color Preferences in a Malaysian Chinese Population - Tan, Kok Wei; Stephen, Ian D. (Frontiers in Psychology, 2019)
Facial skin colour influences the perceived health and attractiveness of Caucasian faces, and has been proposed as a valid cue to aspects of physiological health. Similar preferences for skin colour have previously been found in African participants, while different preferences have been found among mainland Chinese participants. Here, we asked Malaysian Chinese participants (ethnic Chinese living in an Asian country with high levels of exposure to Western culture) to manipulate the skin colour of Malaysian Chinese, Caucasian and African faces to make them “look as healthy as possible”. Participants chose to increase the skin yellowness in a greater extent than increment in redness to optimise healthy appearance. The slight reduction in skin lightness chosen was not statistically significant after correction for multiple comparisons. While broadly in line with the preferences of Caucasian and African participants from previous studies, this differs from Chinese participants. There may be a role for culture in skin colour preferences, though methodological differences mean that further research is necessary to identify the cause of these differences in preferences.